Interpreting the Qurʾān with the Bible (Tafsīr al-Qurʾān bi-l-Kitāb) : Reading the Arabic Bible in the Tafsīrs of Ibn Barraǧān and al-Biqāʿī - III, R. Michael McCoy, (Biblia Arabica ;, 2021)
In Interpreting the Qurʾān with the Bible , R. Michael McCoy III brings together two lesser known yet accomplished commentators on the Qurʾān and the Bible: the muʿtabir Abū al-Ḥakam ʿAbd al-Salām b. al-Išbīlī (d. 536/1141), referred to as Ibn Barraǧān, and qāriʾ al-qurrāʾ Ibrāhīm b. ʿUmar b. Ḥasan al-Biqāʿī (d. 885/1480). In this comparative study, comprised of manuscript analysis and theological exegesis, a robust hermeneutic emerges that shows how Ibn Barraǧān's method of naẓm al-qurʾān and al-Biqāʿī's theory of ʿilm munāsabāt al-qurʾān motivates their reading and interpretation of the Arabic Bible. The similarities in their quranic hermeneutics and approach to the biblical text are astounding as each author crossed established boundaries and pushed the acceptable limits of handling the Bible in their day.